Big cats in borderlands: challenges and implications for transboundary conservation of Asian leopards - Farhadinia, M; Rostro-García, S; Feng, L; Kamler, J; Andrew, S; Elena, S; Igor, K; Mohammed, A; Jianping, G; MacDonald, D (Cambridge University Press, 2020)
Large carnivores have extensive spatial requirements, which often result in ranges that span geopolitical borders. Consequently, management of transboundary populations is subject to different political jurisdictions, often with high heterogeneity in conservation challenges. In continental Asia, there are four endangered leopard subspecies with transboundary populations spanning 23 countries: the Persian, Indochinese, Arabian, and Amur leopards. We reviewed the status of these subspecies and examined their conservation challenges and opportunities. Amur and Indochinese leopards had the majority (58-100%) of their remaining range in borderlands, whereas Persian and Arabian leopards had a quarter (23-26%) of their remaining ranges in borderlands. Overall, in 18 of 23 countries the majority of the remaining leopard range was in borderlands, thus in most countries their conservation is dependent on transboundary collaborations. However, we found only two transboundary initiatives for Asian leopards. Overall, we highlighted three key transboundary landscapes in regions which are of high importance for the survival of these subspecies. Recent listing of leopard in the Bonn Convention is an encouraging step forward, but more international collaboration is needed to save these subspecies. Our paper provides a spatial framework on which range countries and international agencies can establish transboundary cooperation for conserving endangered leopards in Asia.